Sex Steroids and Osteoarthritis: A Mendelian Randomization Study - Yan, Yi-Shang; Qu, Zihao; Yu, Dan-Qing; Wang, Wei; Yan, Shigui; Huang, He-Feng (Frontiers in Endocrinology, 2021)
Objective Sex steroids are thought to contribute to the pathogenesis of osteoarthritis (OA). This study investigated the causal role of sex steroids in site- and sex-specific OA and risk of joint replacement surgery using the Mendelian randomization (MR) method. Methods Instrumental variables for estradiol, dehydroepiandrosterone sulfate, testosterone (T), and dihydrotestosterone (DHT) were selected. We used the inverse variance weighting (IVW) approach as the main MR method to estimate causal effects based on the summary-level data for OA and joint replacement surgery from genome-wide association studies (GWAS). Results A positive causal association was observed between serum T level and risks of hip OA (odds ratio [OR]=1.558, 95% confidence interval [CI]: 1.193–2.034; P=0.001) and hip replacement (OR=1.013, 95% CI: 1.008–1.018; P=2.15×10−8). Serum DHT level was also positively associated with the risk of hip replacement (OR=1.011, 95% CI: 1.006–1.015; P=4.03×10−7) and had potential causality with hip OA (OR=1.398, 95% CI: 1.054–1.855; P=0.020). Conclusions Serum T and DHT levels may play causal roles in the development of hip OA and contribute to the risk of hip replacement, although the underlying mechanisms require further investigation.